Curriculum Modernization in Nepal: Responding to the 21st Century Skills - Singh, Dr. Renu Kumari (Journal of Innovation in Education and Social Research, 2024)
The 21st century has ushered in significant changes in educational paradigms, necessitating a shift towards modernized curricula that equip students with skills required for the contemporary world. This paper explores the modernization of the curriculum in Nepal, focusing on how it addresses the 21st-century skills needed for students to thrive in an evolving global landscape. It examines the current state of the Nepali curriculum, identifies gaps and challenges, and discusses strategies for integrating essential skills such as critical thinking, creativity, digital literacy, and collaboration. The paper also highlights case studies and international best practices to offer a comprehensive overview of curriculum reform efforts.